Analysis Of Metaphorical Expressions On Everlasting Love Songs - Sholichati, Nurdiana, Dra. Malikatul Laila, M.Hum, Drs. Sigit Haryanto, M Hum (2013)
This research is aimed at describing and explaining the linguistic forms of metaphorical expressions, identifying the types and the meaning of metaphorical expressions by integrated based on Human Perceptual System according to Michael C. Haley. In achieving the objective, the writer uses descriptive qualitative as the type of research. The data are metaphorical expressions on everlasting love songs lyrics. In collecting the data, the writer uses documentation methods and the steps are reading and learning from the lyrics of song, selecting the lyrics that contain metaphor, selecting the metaphorical expressions found in lyrics of song and the last is classifying the data. The technique of data analysis is using Michael C. Haley‟s theory. The result of this research paper shows that there are two kinds of linguistic forms. They are phrase and sentence. From twenty data, the writer categorizes it into noun phrase (1 datum) and declarative sentence (19 data). The writer found six categories of Human Perceptual System on everlasting love songs that include abstract, cosmos, energy, terrestrial, thing, and man concept. It contains abstract (10%), energy (15%), substance (5%), terrestrial (10%), thing (15%), and man concept (45%). The meaning from all the metaphorical expression mostly talks about how love can be the inspiration and motivation to face the life